2023
DOI: 10.1021/acsami.2c21232
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Dot Light-Emitting Diodes Exhibiting Narrow-Spectrum Green Electroluminescence by Using Ag–In–Ga–S/GaSx Quantum Dots

Abstract: Quantum dots (QDs), which have high color purity, are expected to be applied as emitting materials to wide-color-gamut displays. To enable their use as an alternative to Cd-based QDs, it is necessary to improve the properties of QDs composed of low-toxicity materials. Although multielement QDs such as Ag–In–Ga–S are prone to spectrally broad emission from defect sites, a core/shell structure covered with a GaS x shell is expected to enable sharp emission from band-edge transitions. Here, QD light-emitting dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
(89 reference statements)
0
21
0
Order By: Relevance
“…Tsuzuki et al reported a GaS x -passivated AIGS QD, whose defect sites are compensated, and the defect-related direct electron injection are suppressed. As shown in Figure e, the fabricated QLED demonstrated a narrowest green electronic emission (33 nm) . For red LEDs, a common strategy is fabricating with CIS/ZnS QDs as luminous layer, whose strong DAP emission and high PLQY are beneficial to LEDs with low turn-on voltage (2.8 V) and high EQE (3.36%) (Figure f) .…”
Section: Led Applicationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Tsuzuki et al reported a GaS x -passivated AIGS QD, whose defect sites are compensated, and the defect-related direct electron injection are suppressed. As shown in Figure e, the fabricated QLED demonstrated a narrowest green electronic emission (33 nm) . For red LEDs, a common strategy is fabricating with CIS/ZnS QDs as luminous layer, whose strong DAP emission and high PLQY are beneficial to LEDs with low turn-on voltage (2.8 V) and high EQE (3.36%) (Figure f) .…”
Section: Led Applicationsmentioning
confidence: 97%
“…Because of the high formation energy of I–III–VI QDs and derivatives, the mainstream strategies of synthesizing QDs are still based on high temperature and organic phase medium, which produce QDs with good dispersion, excellent optical properties, high crystallinity, and high PLQY (∼90%). The methods reported currently can be divided into hot-injection (HI), one-pot heating-up (HU), and single-source precursor thermal pyrolysis. The HI method is the most adopted method for synthesizing quaternary/quinary QDs and especially shows great advantages in precisely constructing core/shell structure. The HU method may show superiority in the uniform nucleation and growth of QDs, and the reaction results can be controlled just by adjusting reaction temperature and precursor ratio.…”
Section: Synthesis and Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, eco-friendly I–III–VI QDs and derivatives (I: Ag + , Cu + ; III: Ga 3+ , In 3+ , Al 3+ ; VI: S 2– , Se 2– , and Te 2– ) have emerged as an excellent alternative for Cd- and Pb-based QDs. The characteristics of direct band-gap semiconductors, band structure tunability, and excited-state energy convergence endow I–III–VI QDs with the potential to realize full visible coverage, pure color, and high PLQY. However, the multitype vacancies, highlighted as V Ag and V S in typical Ag–In/Ga–S QDs, could be nonradiative centers to quench active excitons (Figure a). The resulting inhomogeneous carrier distribution severely limits the improvement of color purity and efficiency in materials and devices.…”
Section: Introductionmentioning
confidence: 99%